Hearing impairment and contributing factors among fertilizer factory workers - Mohammad Saffree Jeffree; Noorhassim Ismail; Khamisah Awang Lukman (Japan Society for Occupational Health/Nihon Sangyo Eisei Gakkai, 2016)
INTRODUCTION: Hearing impairment remains the main occupational health problem in the manufacturing industry, and its contributing factors have not been well controlled.